{Transverse Vaginal Septum with a Hemiuterus: A Laparoscopic-Guided Abdominoperineal Approach.} - Kalampalikis, Andreas; Michala, Lina; Kathopoulis, Nikolaos; Kypriotis, Konstantinos; Papaioannou, Georgia; Protopapas, Athanasios (Journal of pediatric and adolescent gynecology, 2020)
BACKGROUND: Transverse vaginal septum is a rare Müllerian anomaly that can coexist with other defects. CASE: A 12-year-old patient was referred to our clinic for cyclic, lower abdominal pain. Magnetic resonance imaging revealed the presence of a transverse vaginal septum, a hemiuterus with a nonfunctioning rudimentary horn, and left unilateral ureter and kidney. The septum was excised laparoscopically assisted by a vaginal dilator to guide the dissection. The mucosal gap of the vagina was then bridged with sutures using the perineal approach. The postoperative course was uneventful and the patient was discharged with instructions for vaginal dilations. SUMMARY AND CONCLUSION: Early identification of a transverse vaginal septum and careful planning of the operation can improve the outcome of corrective surgery and prevent possible complications.
Keywords: Abnormalities; Child; Dilatation; Female; Humans; Laparoscopy; Magnetic Resonance Imaging; methods; surgery; Uterus; Vagina